The Making-of and experimental artistic research as didactic resources in the training of filmmakers at the Autonomous University of Aguascalientes - Andrade Zamarripa, Armando (2021)
This text presents the results of an educational intervention in the subject Realization II: Direction of Actors of the Degree in Cinematographic and Audiovisual Arts of the Autonomous University of Aguascalientes through the Making-of as a didactic resource in an autonomous and collaborative learning model based in the experimental artistic research from the creative needs and the type of cinema that its filmmakers in training want to film. The proposal brings together the findings of Pat Brereton, who verified that the consultation of the DVD add-ons allows a learning of cinema outside the classroom, and the theoretical precepts of Daniel Montero who argues that the comprehensive training of artists in universities is achieves with the experimental practice of artistic research for the development of his own epistemologies and methodologies. Therefore, from the extra materials we chose the making-of because it reveals the technical-methodological secret of filmmakers in praxis.